X2+15x=-36

Simple and best practice solution for X2+15x=-36 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for X2+15x=-36 equation:



X2+15X=-36
We move all terms to the left:
X2+15X-(-36)=0
We add all the numbers together, and all the variables
X^2+15X+36=0
a = 1; b = 15; c = +36;
Δ = b2-4ac
Δ = 152-4·1·36
Δ = 81
The delta value is higher than zero, so the equation has two solutions
We use following formulas to calculate our solutions:
$X_{1}=\frac{-b-\sqrt{\Delta}}{2a}$
$X_{2}=\frac{-b+\sqrt{\Delta}}{2a}$

$\sqrt{\Delta}=\sqrt{81}=9$
$X_{1}=\frac{-b-\sqrt{\Delta}}{2a}=\frac{-(15)-9}{2*1}=\frac{-24}{2} =-12 $
$X_{2}=\frac{-b+\sqrt{\Delta}}{2a}=\frac{-(15)+9}{2*1}=\frac{-6}{2} =-3 $

See similar equations:

| (6*e^2)+18=7 | | (1/2x—1)=(4/8x—4) | | 13y=170 | | −18=−12a | | 4.9t^2-24t+11=0 | | −18= −12a | | 16/21=x/18 | | -2x-6=3x+19 | | 16x=-2x+5 | | 10x−3=8+10x | | 2(x+2-6=10-3(x-1) | | (2x-3)/(3)+(4x)/(3)=7 | | n-3/4-11/6=21/3 | | 2x=16.9 | | x➗11.2=17 | | 12x–10=26 | | 4(3x+1=28 | | x+.75x=6 | | F(x)=-2x^2+8x-1 | | 2(x+5)=(x+5)2 | | 2x+5=(x+5)2 | | (2w-3)w=14^2 | | 7x2-49=0 | | 5(u+4)-8u=38 | | 41x+372=560 | | 20-3/4x=10 | | 4x=16. | | 1/2x+14-9/x+7=6 | | 6d−d=15 | | 6(2+x)+5x=86 | | 5x-27x+6=0 | | (16)^(2x+1)=128 |

Equations solver categories